PEMBERDAYAAN PEGAWAI DI PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - DEWI BUNTUANG, PRICYLIA CHINTYA (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to analyze employee empowerment in Central Sulawesi Provincial Government. This research is designed descriptively. The location of this research is at work unit of local government area of Central Sulawesi Province by taking employee as population. The number of research samples 308 respondents were determined by stratified random sampling technique. Data collection techniques in this study consist of observation, questionnaires and documentation. The result of the research shows the whole dimension under study, the most powerful dimension in forming employee empowerment in Central Sulawesi Provincial Government is the impact dimension (85,6%) because in that dimension state that decision and action of employee have influence in organization, while the low dimension is dimension meaning (84.9%) because the dimension states that employees are less empowered and trusted in the job. The results can also be interpreted that with the empowerment of employees, the result of empowerment makes the decisions and actions of employees to be influential in the organization, but overall employees tend to be less empowered and trusted in carrying out their work.